Impact of HPAI on the Ghanaian economy - Diao, Xinshen (International Food Policy Research Institute, 2008)
From April to June 2007, there were three highly pathogenic avian influenza (HPAI) outbreaks in Ghana, which were effectively controlled by the Veterinary Services Directorate of the Ministry of Food and Agriculture. Even though information is available on some of the economic costs of these outbreaks (such as the costs of disease control), information on the economy-wide losses suffered is limited. To fill this gap, we developed a dynamic computable general equilibrium (DCGE) model and used a recent (2005) detailed social accounting matrix to estimate the economy-wide impacts of different HPAI outbreak scenarios.